Place-Based Policies in Indonesia : A Critical Review - Rothenberg, Alexander D.; Temenggung, Della (World Bank, Washington, DC, 2019)
Place-based policies target specific geographic areas for special treatment. They attempt to stimulate growth and development in lagging regions by (1) attracting firms, (2) attracting workers and human capital, and (3) improving local public goods. This report conducts a critical review of place-based policies that have been implemented in Indonesia since Suharto's presidency. It examines the evolution of different policies and programs, aiming to understand whether these programs have increased prosperity, improved livability, or promoted greater inclusiveness for lagging regions. We begin by describing the evolution of central and local policymaking in Indonesia, providing the context through which place-based policies operate. We then review place-based policies that affect firm location choices, improve schooling and health for workers, and provide social assistance for people in lagging areas, evaluating their strengths and weaknesses. We conclude by offering recommendations to improve and redirect place-based policymaking in the future.